Shifting Attitudes Toward English Learning: A Longitudinal Study of High School Students in a Rural Setting - FIRJATULLAH PUTRA RAMADHAN; Daniar Sofeny (LPPM Universitas Islam Darul `Ulum Lamongan, 2026)
This study aims to analyze changes in attitudes of high school students in rural areas towards learning English using a qualitative descriptive approach through literature study. Students' attitudes towards English are an important aspect in successful learning, which is influenced by pedagogical, social, and emotional factors. Through an analysis of various academic literature sources, this study found that students' attitudes tend to change positively over time when supported by a communicative, contextually relevant learning approach, and involving the use of interesting media.The results also indicate that more self-confidence, teacher support, peer interaction, and support of family collectively increased students’ motivation of learning English. Those students with low socioeconomic status had the most positive changes in attitudes in inclusive and supportive learning environments.The study highlights that learning attitudes are dynamic and impacted by an interconnected combination of internal and external influences. For these reasons, developing educational policies and teaching strategies that take into account the affective side are crucial to developing the success of English learning in rural Indonesia.